Supporting the Performance of Lecturer: The Effect of Competency and Motivation on Lecturer Performance - Wulandari, Aeni Fauziyah; Luturlean, Bachruddin Saleh; Farihin, Farihin (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
Every higher education institution needs to focus on the performance of its lecturers if they want to develop and produce quality education. This research aims to determine the influence of competence and motivation on the performance of lecturers. This research uses a quantitative approach with a causal relationship research design. The population of this study is all lecturers of the Faculty of Education and Teacher Training, IAIN Syekh Nurjati Cirebon, amounting to 168 people. The sample for this study is 63 people. The research data collection instrument uses a questionnaire consisting of 38 statements to measure competence, motivation, and performance. The data analysis for this research uses path analysis with the help of the SPSS program. The results of this study indicate that the significance value of the correlation between competence and motivation is 0.00<0.05, which means that there is a significant relationship between competence and motivation. Then, the results of the correlation testing between competence and motivation towards performance show that the F-value of the influence of competence and motivation on performance is 21.260 with a significance value of 0.00<0.05, which means that competence and motivation simultaneously have a significant influence on lecturers' performance. Thus, competence and motivation support lecturers in achieving performance.